Developing and Broadcasting an English Podcast on RRI’s ‘CERIWIS’ Program: A Case Study - Tiva Ramadhani Nur Fahmi (Jurnal Vokasia, 2024)
The job training report entitled "Broadcasting An English Podcast On RRI’s Program “Ceriwis”" is designed to provide detailed information of the internship process carried out at RRI Purwokerto, specifically focusing on the development and production of an English-language podcast. The internship offered in-depth experience in the broadcasting field, particularly with the CERIWIS podcast. This project went through several stages, starting with pre-production, which involved planning the podcast concept, developing the storyline, and securing approval from the supervisors. The production stage took place in the podcast studio with the assistance of the TMB team, and the recording itself featured smooth conversations between the host and speaker, including impromptu discussions that added a natural flow to the podcast. The post-production phase included editing the audio and video, adding subtitles, special effects, and a flyer introduction that presented information about the podcast’s topic, host, and speaker. Despite facing various obstacles during each stage, such as scheduling conflicts and issues with videography, the project was successfully completed. The purpose of the project was to contribute to RRI Purwokerto’s content library, targeting young audiences with relatable and lighthearted conversations. The internship also provided valuable insights into the challenges and potential improvements for RRI Purwokerto, particularly in diversifying its content and engaging a wider audience.